Smart Lighting System for a Classroom using Solar PV and Internet of Things (IoT) - Mohd Alias, Muhamad Ezzwan; Salimin, Suriana (Evolution in Electrical and Electronic Engineering, 2023)
Nowadays, all schools around Malaysia still rely upon the continuity of power supply from Tenaga Nasional Berhad (TNB) to operate the lighting system in the classroom. Therefore, when power outages occur, the school's lighting system is unable to operate since the power outages usually happen without prior notification in advance by TNB. This main issue should be prioritized with utmost importance to ensure the learning and teaching session can be conducted effectively. Therefore, the development of a smart lighting system for a classroom using solar PV and the Internet of Things (IoT) is designed to tackle this issue. The project was composed of a stand-alone off-grid photovoltaic system, which used a battery to power up the lighting system and integrated it with the implementation of the IoT system. The IoT system comprised two features: controlled the lighting system and monitored the illuminance level from the emitted light wirelessly. Hence, the project intended to design and simulate a power converter inverter circuit output voltage from 12V DC to 220V AC, to control the lighting system as well as monitor the illuminance level by accessing through the Blynk application. A mini-scale classroom prototype consisting of the solar PV system and integration of an IoT system is also being developed. The prototype development involves a monocrystalline solar panel, sealed lead-acid battery, solar charge controller, LED bulbs, ESP8266, 4-relay channel module, digital BH1750 light sensor, and digital lux meter. The results accuracy of the measurement apparatus is 87.30% for the digital BH1750 light sensor and 83.57% for the digital lux meter interpreted that the system effectively monitored the illuminance level of the LED bulbs in the classroom